The Role of Familiarity Bias and Confirmation Bias in Investment Decisions: The Moderating Role of Financial Literacy - A Case Study of FEB Students at Universtas Klabat - Lionardo, Holly Christy; Resubun, Laura Alicia; Sahetapy, Kenneth August (Jurnal Economic Resource, 2025)
This study examines the influence of familiarity bias and confirmation bias on investment decisions, with financial literacy as a moderating factor, involving 293 students from the Faculty of Economics and Business (FEB) at Universitas Klabat. The findings indicate that familiarity bias significantly affects investment decisions, meaning that the tendency to choose familiar investments influences students' financial choices. Conversely, confirmation bias does not have a significant effect, suggesting that the inclination to focus solely on information that aligns with personal beliefs has a limited impact on their investment decisions. Additionally, the findings reveal that financial literacy reduces the influence of familiarity bias, enabling students to make rational decisions. However, financial literacy does not moderate the relationship between confirmation bias and investment decisions. This study underscores the importance of financial literacy in formal education. Integrating comprehensive financial literacy materials into the curriculum could help students mitigate investment biases and enhance the quality of their financial decisions, especially in a complex economic environment.